Evaluation of Visual Based Augmented Reality (AR) Learning Application (V-ARA-Dculia) for Dyscalculia Learners - Kohilah Miundy; Halimah Badioze Zaman; Aliimran Nosrdin; Kher Hui Ng (JOIV : International Journal on Informatics Visualization, 2019)
The rapid growth in technology have affected processes in various domains such as business, healthcare, agriculture and education. Computer related applications used in these domains are available so easily, that it is impossible to imagine a situation without them. Technologies that were available but hardly commonly used a few decades ago such as Virtual Reality (VR) and Augmented Reality (AR) have now become technologies that are fast gaining interests in most fields including service related1 fields such as healthcare and education. The basic idea of AR is to superimpose sense enhancements over a real-world environment. It is a perfect solution for learners with learning difficulties as it combines the advantages of multi senses of the learners, helps them to understand learning better when the integration of both virtuality and reality is embedded in their learning applications. AR is mostly effectively used when computer generated visual enhancements are integrated into real life applications. Thus, this paper highlights the evaluation of the visual-based AR learning application to investigate its plausible assistive functions that can help dyscalculia learners learn Mathematics in a more meaningful way. Findings of the study showed that the students who had difficulties on memory, abstraction, sequencing processing, motor and visual perception, found the visual-based Augmented Reality (AR) Â technology embedded in an application, a positive assistive learning application that can help dyscalculia learners learn mathematics more effectively. Â Â